KEPUASAN LAYANAN KESEHATAN POLI UMUM DI RSIA ARAFAH ANWAR MEDIKA SUKODONO SIDOARJO - Nur Ilahi Anjani (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2018)
This study aims to determine the satisfaction of patients in using health services at general poly hospital of Arafah Anwar Medika Sukodono in Sidoarjo. The survey was conducted on 50 new patients who received health services at Polia General Hospital Anwar Medika Sukodono Sidoarjo Regency. Instruments are structured questionnaires through PSQ (Patient Satisfaction Questionnaire). Data were analyzed using descriptive statistical test through the frequency distribution table. Research shows the satisfaction of respondents to service in general poly in general and the satisfaction of respondents related to facilities in the general poly is good. Satisfaction of respondent to physician ability and doctor's accuracy is good. Satisfaction of respondent to attitude of doctor and nurse to patient have good. Satisfaction of respondent on giving information from doctor have good. Satisfaction of respondents related to the conformity of cost is good. Satisfaction of respondents at the time of examination is also good. And the satisfaction of respondents related to the access of respondents is good. This research recommends follow-up related inputs, suggestions, complaints from the public related to the service so as to provide the best solution to the problems faced by customers and conduct regular and continuous surveys to maintain the quality of service.